Stochastic service network design for transportation planning of consolidation carriers - Jiang, Xiaoping (2020)
Service network design (SND) has long been used in freight transportation to assist consolidation carriers with tactical planning. Defined on a directed graph, SND entails deciding which arcs to open and how to route commodities on selected arcs, so that customers' shipping demands are met at minimum cost. Most studies on SND assume that customers' demands are known with certainty. This assumption is rarely observed in real-life applications, however. Indeed, consolidation carriers are often faced with demand uncertainty at the decision-making point. In order to build a robust service network that functions well for various demand realizations, it is necessary to take demand uncertainty explicitly into account. SND with demand uncertainty is referred to as stochastic service network design (SSND). Despite its significance, SSND has received relatively little attention by the research community due to its intractability. This thesis advances the research on SSND in three respects.